Between Mask and Uniform: The Undecidability of Mimesis. Issue 1 (April 2022) - Belo, Sara
Abstract : In this essay I address the problem of identity formation posed by our mimetic condition by considering the relationship between art, domination, and liberation. To better understand how the artistic gift can engender liberation, even if permanently at risk of being instrumentalised for domination, I propose an analysis of the differences between an artistic mask and a uniform. More specifically, I focus on how each of these mimetic forms mobilise different kinds of actions due to the different conceptions of identity that underlie them: the temporary result of an instance of identification among many others, in the case of the artistic mask, and a permanent stabilisation, in the case of the uniform. I ground this differentiation in an analysis of the film Der Hauptmann (2018) by Robert Schwentke and on readings of Philippe Lacoue-Labarthe and Jean-Luc Nancy's critique of 'The Nazi Myth' (1990) constitutive of the mimetic turn.